Pengaruh Penambahan POME Terhadap Konsentrasi N, P, K Pada Proses Pengomposan Tandan Kosong Sawit - Mora Rahmayuanda; Adrianto Ahmad; David Andrio (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The palm oil industry is currently experiencing very rapid development which is marked by an increase in CPO production. The main solid waste produced by the palm oil processing industry is Empty Fruit Bunch (EFB) which is 22-23%. The composting process is one of the processing methods that can be done on EFB waste, however, the composting process requires a long time. Therefore, it is important to do a breakthrough to speed up the processing time. In this study, composting can be accelerated by adding mixed cultures and POME as a source of nutrition. The purpose of this study was to determine the effect of variations in POME addition on windrow aerob composting of EFB on the quality of N, P, K. In composting process takes place with variations by adding POME 0%, 20%, 30%, and 40%. The results of the study showed that the effect of POME 40% addition gave the best results as indicated by the highest N, P, K content of 2.41%, 2.29%, 2.56%, temperature 33.61OC, pH 6.84, and water content 49.4%, and compost produced meets SNI 19-7030-2004 compost quality standards. Thus, the performance of composting with the best result is with the addition of 40% POME with 25 days composting time. Utilization of oil palm empty fruit bunches is one of the solutions to sustainable environmental pollution control.Key Word : Composting Process, Empty Fruit Bunch, NPK, Palm Oil Mill Effluent (POME), Windrow.